Temperature induced self-healing properties of alginate gelatin hydrogels - Greco, Immacolata; Vadakken Gigimon, Anet; Varon, Carolin; Madevska Bogdanova, Ana; Iorio, S.Carlo (Elsevier, 2024)
One of the main challenges in tissue engineering is developing constructs that restore damaged tissues. This has led to the growth of classes of materials with tuneable mechanical and absorption properties. Among others, hydrogels are particularly fascinating because they can be functionalized to self-repairdamage like the native living tissues. This work proposes an improved thermo-responsive alginate-gelatine (SA-Gel) hydrogel capable of self-repairing, whose mechanical properties are enhanced by the addition of optimal concentration of graphene oxide (GO). The initial results show that the novel hydrogel’s formulation improves self- healing and mechanical properties making them a potential candidate for biomedical applications.
Keywords: Bioengineering; alginate-gelatine; tissue engineering